Analysis of TaeCheongsu natural water from Baegunsan Mountain, Korea - Jaswir, Irwandi; Octavianti, Fitri; Lestari, Widya; Hendri, Ridar (BioCore Online Publishing, 2016)
Water with special healing properties has been reported for generations to contain health benefi ts and abilities to cure diseases. Water from locations including Nordenau in Germany and Lourdes in Paris have been analysed to deduce the special characteristics of the water that provide the healing properties. In this study, natural bedrock underground water from Baegunsan mountain in Idong- myeon, Pocheon- si, Gyeonggi- go, Korea was analysed for benefi cial properties. The alkalescent hydrogen-water which is termed TaeCheongsu water was tested for superoxide anion radical scavenging activities (SOSA), size of water molecules, active hydrogen content, hydrogen peroxide degradation capability and dissolved oxygen content. The results for TaeCheongsu water was compared against tap water, Stephan water, Nordenauer water and Lourdes water. TaeCheongsu water showed superior results compared to other healing waters and against controls across all tests. Therefore, TaeCheongsu healing water is a high quality water with potential benefi ts for health.